ALPHA PSYCHIATRY 2022
DOI: 10.5152/alphapsychiatry.2022.22840
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive Therapy in Patients with ObsessiveCompulsive Disorder: A review

Abstract: Metacognitive therapy is a relatively novel and growing psychotherapeutic approach. Within the last 20 years, several metacognitive-oriented therapy methods have been developed. They are metacognitive therapy which was developed by Wells, metacognitive training which was produced by Moritz et al. especially for patients with psychotic disorder, and metacognitive reflection and insight therapy for psychotic patients. Among them, the most structured one seems the metacognitive therapy. The main notion of metacog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…However, it has been reported that possible factors include genetics, neurotransmitter abnormalities, infection, and personality traits, and treatment options mainly involve psychotherapy and drug therapy. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that possible factors include genetics, neurotransmitter abnormalities, infection, and personality traits, and treatment options mainly involve psychotherapy and drug therapy. 3 , 4 …”
Section: Introductionmentioning
confidence: 99%